Effect of using dornase alfa versus bronchoscopy as treatment of persistent atelectasis in children with congenital heart disease: a retrospective study - Llaque-Quiroz, Patricia (2023)
Objetives: To evaluate the effect of using dornase alfa versus bronchoscopy as a treatment for persistent atelectasis in children with congenital heart disease. Methods: A retrospective cohort study was carried out with the information in the clinical history of children with congenital heart disease and persistent atelectasis hospitalized at Instituto Nacional de Salud del Niño San Borja in 2016 and 2017, treated with bronchoscopy of dornase alfa. The outcome was the atelectasis score assessed on chest X-ray before and after treatment. Chi2 and paired T-student tests were used to assess the association between the variables. Results: Of the 43 patients, 60.5% received treatment with dornase alfa and the rest underwent to bronchoscopy. 23 (53.5%) patients were women and the median age was 5 months. After performing bronchoscopy, there was a statistically significant decrease in respiratory rate (p<0.05). The radiographic score should be after treatment with dornase alfa an bronchoscopy, from 3.9 (SD: 2.4) to 2.9 (SD: 2.1), p<0.05 and from 5.5 (SD: 2.5) to 3.9 (2.1), p<0.05, respectively. No differences were found in adverse effects after both procedures. Conclusion: Both dornase alfa and bronchoscopy were useful inthe management of persistent atelectasis in children with congenital heart disease without differences in adverse effects.